Portal myofibroblasts promote vascular remodeling underlying cirrhosis formation through the release of microparticles. Issue 3 (22nd January 2015) - Lemoinne, Sara; Cadoret, Axelle; Rautou, Pierre‐Emmanuel; El Mourabit, Haquima; Ratziu, Vlad; Corpechot, Christophe; Rey, Colette; Bosselut, Nelly; Barbu, Véronique; Wendum, Dominique; Feldmann, Gérard; Boulanger, Chantal; et al.
Abstract : Liver fibrosis expanding from portal tracts and vascular remodeling are determinant factors in the progression of liver diseases to cirrhosis. In the present study, we examined the potential contribution of portal myofibroblasts (PMFs) to the vascular changes leading to cirrhosis. The analyses of liver cells based on the transcriptome of rat PMFs, compared to hepatic stellate cell HSC‐derived myofibroblasts in culture, identified collagen, type XV, alpha 1 (COL15A1) as a marker of PMFs. Normal liver contained rare COL15A1‐immunoreactive cells adjacent to the bile ducts and canals of Hering in the portal area. A marked increase in COL15A1 expression occurred together with that of the endothelial marker, von Willebrand factor, in human and rat liver tissue, at advanced stages of fibrosis caused by either biliary or hepatocellular injury. In cirrhotic liver, COL15A1‐expressing PMFs adopted a perivascular distribution outlining vascular capillaries proximal to reactive ductules, within large fibrotic septa. The effect of PMFs on endothelial cells (ECs) was evaluated by in vitro and in vivo angiogenesis assays. PMF‐conditioned medium increased the migration and tubulogenesis of liver ECs as well as human umbilical vein ECs and triggered angiogenesis within Matrigel plugs in mice. In coculture, PMFs developed intercellular junctions with ECs and enhanced the formation of vascular structures. PMFs released vascular endothelial growth factor (VEGF)A‐containing microparticles, which activated VEGF receptor 2 in ECs and largely mediated their proangiogenic effect. Cholangiocytes potentiated the angiogenic properties of PMFs by increasing VEGFA expression and microparticle shedding in these cells. Conclusion : PMFs are key cells in hepatic vascular remodeling. They signal to ECs through VEGFA‐laden microparticles and act as mural cells for newly formed vessels, driving scar progression from portal tracts into the parenchyma. (Hepatology 2015;61:1041–1055)